Students’ Response on Information-Gap Task in Improving Speaking Skill - Yosa Lanovastia; Sofyan A. Gani; Yuliana Natsir (Research in English and Education Journal, 2017)
This descriptive qualitative research was conducted to discover the students’ response towards the implementation of Information-Gap Task in improving speaking skill at SMA Tunas Bangsa, South West Aceh. The subject of this research was 32 studentsof class IX chosen through purposive sampling technique. The data were collected through questionnaire items which was adapted from the formula of Taylor-powell and Bahous, et al. The result of this research showed that most students gave positive response toward the implementation of Information-Gap Task and they agree that Information-Gap Task can help, motivate and attract them in improving speaking skill. Only a few   they do not enjoy the speaking practice through Information-Gap Task. In brief, the implementation of Information-Gap Task by the teacher improves students’ speaking skill and helps students to cope with their speaking problem.